(3GdeONd Edi Yde GdfLhe hCMcGegs - (3YHO GdQMef Hf YeQ Hf Sgd GdUhaj GdQGRqj, CHh GdMSjf,J (B376 (3g` s ((3CMeO Hf eMeO Hf (B( (3GdMGL (B) (3MSjf Hf eMeO GdMcje GdLQLGhi GdCfUGQi GdTGaYi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi aWQ GdYHGO Ydi eYQaJg GdaUd GdChd ai gjFI GdCadGc hYOOgG hYOO GdchGcH s
(3BNQgG (B:s
(3ef BNQ GdHGH GdSGHY BNQ GdehLhO bhdg (B: (3aEf ef GdCTjGA eGdGjchf CbhGJgG cKjQI ef YOO GdTghQ cChbGJ GdhdGOI hefgG s
(3GdcJGH eQJH Ydi NeS ebGdGJs
(3cJHJ gPg GdfSNI Hbde eged GdfbW CMjGfkGs
(3HgG QShe hLOGhds
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs